Feasibility and Domain Validation of RA Flare Core Domain Set: A Report of the OMERACT 2014 RA Flare Group Plenary - Bartlett, Susan J. (J Rheumatol, 2015)
OBJECTIVE: The OMERACT RA Flare Group was established to develop an approach to identify and measure rheumatoid arthritis (RA) flares. Here, we provide an overview of our OMERACT 2014 plenary. METHODS: Feasibility and validity of flare domains endorsed at OMERACT 11 (2012) were described based on initial data from three international studies collected using a common set of questions specific to RA flare. Mean flare frequency, severity, and duration data were presented, and domain scores were compared by flare status to examine known-groups validity. Breakout groups provided input for stiffness, self-management, contextual factors, and measurement considerations. RESULTS: Flare data from 501 patients in a observational study indicated 39% were in a flare, with mean (SD) severity of 6.0 (2.6) and 55% lasting > 14 days. Pain, physical function, fatigue, participation and stiffness scores averaged ≥ 2 times higher (2 of 11 points) in flaring individuals. Correlations between flare domains and corresponding legacy instruments were r’s from 0.46 to 0.93. A combined definition (patient-report of flare and DAS28 increase) was evaluated in two other trials with similar results. Breakout groups debated specific measurement issues. CONCLUSION: These data contribute initial evidence of feasibility and content validation of the OMERACT RA Flare Core Domain Set. Our research agenda for OMERACT 2016 includes establishing duration/intensity criteria and developing criteria to identify RA flares using existing disease activity measures. Ongoing work will also address discordance between patients and physician ratings, facilitate applications to clinical care, elucidate the role of self-management and help finalize recommendations for RA flare measurement.